„Braterstwo krwi”. Historia Stanisława Aronsona - Ratajczak, Wiesław (My University, 2013)
Based on conversations with the hero, Patrycja Bukalska’s "Rysiek z Kedywu. Niezwykłe losy Stanisława Aronsona" [Rysiek from Kedyw. Incredible Tribulations of Stanisław Aronson], is an important contribution to the study of Polish-Jewish relations. This is because Aronson’s life is a unique combination of various elements of Polish and Jewish biographies in the 20th century. His life story includes: a happy childhood in a wealthy assimilated Jewish family, the nightmare of Soviet and German occupation, deaths of closest relations, participation in Armia Krajowa resistance movement and Warsaw Uprising, military service in general Anders’s corps, and then in Israeli army. Jew, Pole, Israeli: each of these identies demanded a different ordering and expression of memory, different omissions and declarations. With such an unusual and mixed experience, Aronson had a vantage point to look at the images that Poles, Jews, Holocaust survivors and citizens of newly created Israel, had of one another. Bukalska’s book can be read as a voice against generalizations, as a narrative about a concrete human life immersed in history, a narrative about individual choices, courage, and friendship.
„Brotherhood of Blood”. A History of Stanisław Aronson
Keywords: war literature; identity; Polish-Jewish (and Jewish-Polish) relations; biography; military ethos